Peran Bahasa Arab Melayu dalam Melestarikan Warisan Budaya dan Identitas di Aceh Besar - Fairuz Sakinata; Sri Mawaddah (Pustaka Digital Indonesia, 2025)
The urgency of this research lies in preserving the cultural heritage and identity of Aceh Besar through the Arabic-Malay language. Language is an integral part of a society's culture and identity. In Aceh Besar, the fusion of Arabic and Malay has created a distinctive pattern in communication, literature, and religious practices. This research aims to examine the role of the Arabic-Malay language in preserving the cultural heritage and identity of the Aceh Besar community. The Arabic-Malay language functions not only as a means of daily communication but also as an essential medium for transmitting cultural and religious values deeply embedded in the local way of life. Traditional educational institutions such as dayah play a crucial role in passing on the use of Arabic-Malay to younger generations through the teaching of kitab kuning (classical Islamic texts) and oral tradition practices. Moreover, classical Arabic-Malay manuscripts preserved in Aceh Besar serve as a rich intellectual heritage, containing religious teachings, customary laws, and historical records that strengthen the local cultural identity. This study employs a qualitative descriptive approach using in-depth interviews, participatory observation, and literature review. Data analysis is conducted qualitatively through data reduction, presentation, and verification processes to gain an in-depth understanding of the function of the Arabic-Malay language in preserving culture and identity. The findings indicate that the Arabic-Malay language serves as a main pillar in maintaining the continuity of cultural values and Islamic identity in Aceh Besar. Therefore, the preservation of this language is vital in sustaining an authentic and enduring local cultural heritage.